Botanicals: a natural approach to control ascaridiosis in poultry - SYMEONIDOU, I.; BONOS, E.; MOUSTAKIDIS, K.; FLOROU-PANERI, P.; CHRISTAKI, E.; PAPAZAHARIADOU, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Parasites (protozoa, helminthes, arthropods) represent a main threat for poultry worldwide. Among helminthes, nematodes constitute the most important group of parasites of poultry. The nematode Ascaridia galli, the cause of ascaridiosis in poultry, is one of the most important and prevalent parasites, resulting in serious economic losses, associated with the treatment cost, the decreased feed efficiency, and the poor egg and meat production. During the past few decades the indiscriminate use of anthelmintic drugs has generated several cases of resistance in helminthes in poultry, situation which is coupled with the severity of residues in poultry products. For this reason, nowadays attention has been drawn to the use of botanicals in poultry diet, due to their anthelmintic properties. Furthermore, the dietary use eco-friend ly of these plant derived substances compared to conventional synthetic anthelmintic drugs is considered as a natural and ecofriendly approach by the consumers. The focus of the present review is to recapitulate the studies, both in vivo and in vitro, that have demonstrated the anthelmintic efficacy of various dietary botanicals in controlling poultry ascaridiosis.